Bilateral total hip arthroplasty in a young man with hereditary multiple exostoses. (5th January 2015) - Vaishya, Raju; Swami, Sandeep; Vijay, Vipul; Vaish, Abhishek
Abstract : We report a rare case of a young man with hereditary multiple exostoses (HME) who presented with severe pain in the hips, requiring bilateral total hip arthroplasty (THA), along with excision of the exostoses. The reported incidence of exostoses around the hip has been reported from 30% in some series to 90% in other studies of HME. These patients may remain asymptomatic, but if not, their symptoms are usually related to the presence of the exostoses itself and the possibility of hip osteoarthrosis is frequently overlooked. This may account for a low incidence of THA for this condition. Surgical management often remains challenging as such lesions are not commonly encountered in the clinical practice and are often very difficult to treat.